State, market, and religions in Chinese societies - Yang, Fenggang; Tamney, Joseph B. (Religion and the social order, 2005)
This collection of original, new studies about Mainland China and Taiwan focuses on religious changes, and especially the role of the state and market in affecting religious developments in these societies. Information was gathered by participant observation and interviews primarily, and the analysis of documents secondarily. The topics covered are: the growing interest in the study of religion, the methods used by Christians to be able to coexist with a communist government, revival techniques being used by Buddhist monks, the strategies of Daoist priests and sect leaders to attract followers, the significance of mass-circulating morality books, and the ongoing debate about the significance and nature of Confucianism. The book will interest social scientists, religious specialists, journalists, and others who want to understand the changing nature of Chinese societies, and those interested in religious change in modernizing societies